Concentration Variability of Water-Soluble Ions during the Acceptable and Exceeded Pollution in an Industrial Region - Švédová, Barbora; Raclavská, Helena; Kucbel, Marek; Růžičková, Jana; Raclavský, Konstantin; Koliba, Miroslav; Juchelková, Dagmar (International journal of environmental research and public health, 2020)
This study investigates the chemical composition of water-soluble inorganic ions at eight localities situated in the Moravian-Silesian Region (the Czech Republic) at the border with Poland. Water-soluble inorganic ions were monitored in the winter period of 2018 (January, 11 days and February, 5 days). The set was divided into two periods: the acceptable period (the 24-h concentration of PM10 < 50 µg/m3) and the period with exceeded pollution (PM10 ˃ 50 µg/m3). Air quality in the Moravian-Silesian Region and Upper Silesia is among the most polluted in Europe, especially in the winter season when the concentration of PM10 is repeatedly exceeded. The information on the occurrence and behaviour of water-soluble inorganic ions in the air during the smog episodes in Europe is insufficient. The concentrations of water-soluble ions (chlorides, sulphates, nitrates, ammonium ions, potassium) during the exceeded period are higher by two to three times compared with the acceptable period. The major anions for both acceptable period and exceeded pollution are nitrates. During the period of exceeded pollution, percentages of water-soluble ions in PM10 decrease while percentages of carbonaceous matter and insoluble particles (fly ash) increase.
Keywords: Environmental Monitoring; particulate matter; Particle Size; Particulate Matter; pevné částice; monitorování životního prostředí; Poland; Česká republika; voda; Europe; air pollution; Air Pollution; látky znečišťující vzduch; Czech Republic; Evropa; meteorological parameters; znečištění ovzduší; roční období; Seasons; velikost částic; ionty; Ions; enrichment factor; Polsko; water-soluble inorganic ions; Water; Air Pollutants